COMPARATIVE EFFICACY AND TOLERABILITY OF AVOCADO / SOYBEAN UNSAPONIFIABLES AND THEIR COMBINATION WITH INTRA-ARTICULAR HYALURONIC ACID IN PATIENTS WITH KNEE AND HIP OSTEOARTHROSIS - Ye. I. Shmidt; I. V. Belozerova (Klinicist)
Objective: to evaluate the comparative efficacy and tolerability of avocado / soybean unsaponifiables (ASU) and their combination with intra-articular hyaluronic acid in patients with knee and hip osteoarthrosis (OA).Subjects and methods. A randomized observational non-interventional non-placebo controlled trial was conducted. It included 18 patients who were randomized to 2 groups with 9 in each. One patient group took only ASU along with nonsteroidal anti-nflammatory drugs (NSAIDs); the other received ASU in combination with intra-articular hyaluronic acid. Their treatment was performed for 6 months, followed by a 6-month follow-up. The results were assessed by the WOMAC index. Account was taken of the opinions of a patient and his / her physician on therapeutic effectiveness, as well as altered needs for NSAIDs during treatment and after the follow-up.Results. There was a gradual reduction in joint pain, stiffness, and dysfunction (as shown by the visual analog scale) in both groups just one month posttherapy. This trend remained for 3 months. After 6 months of therapy, there were slight increases in the values of joint pain, stiffness, and dysfunction in the combined therapy group whereas the values continued to decrease in the monotherapy group. Six months after termination of treatment, the examined values doubled in the ASU monotherapy group and remained at posttreatment visit levels in the combined therapy group. Just the same, six months after termination of 6-month therapy, both groups displayed the significantly lower values of pain, stiffness, and dysfunction than those prior to treatment. ASU used both alone and in combination with hyaluronic acid was noted to be well tolerated. The considerable reduction in the needs for NSAIDs in both groups and, in a number of cases, the possibility of reducing their intake proved the efficiency of ASU used alone and in combination with hyaluronic acid. The important result of this trial was the good tolerability of both test drugs.Conclusion. The results of the performed trial provided support for the efficacy of ASU in treating both moderate and severe knee and hip OA. Hyaluronic acid in combination with ASU ensures a longer duration of the achieved effect than that of ASU monotherapy (during 12 months, a minimum of 6 months after termination of treatment) regardless of the severity and duration of OA.